2021
DOI: 10.1093/police/paab007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lockdown on Police Service Calls During the COVID-19 Pandemic in China

Abstract: Police service calls have been studied widely in the Western context, but they are rarely discussed in the Chinese context. For the context of this study, it is important to note that the Chinese authorities implemented the strictest lockdown after the COVID-19 pandemic began. Drawing on the data from a county-level city in Hubei province, this study examines changes in the quantity and nature of 110 service calls before, during, and after the COVID-19 pandemic lockdown. The results indicate that the average w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
(74 reference statements)
0
33
2
1
Order By: Relevance
“…The data utilized for this study are the daily counts of calls for police service that were reported to the local Police Bureau and kept in the Computer Aid Dispatch system (CAD) from an anonymous medium-sized city 8 (M1-city hereafter) located in south China. Although the calls to police data is a subset of all recorded crimes in the city, it does provide a good measure of crime during the pandemic period, one that has been used in other COVID-19/crime-related studies (Bullinger et al, 2020 ; Dai et al, 2021 ). The data includes eight typical property offenses: automobile theft, electromobile (also referred to as electric scooters) theft, motorcycle theft, bicycle theft, theft from automobiles, residential burglary, cyber-fraud, and pickpocketing.…”
Section: Methodsmentioning
confidence: 99%
“…The data utilized for this study are the daily counts of calls for police service that were reported to the local Police Bureau and kept in the Computer Aid Dispatch system (CAD) from an anonymous medium-sized city 8 (M1-city hereafter) located in south China. Although the calls to police data is a subset of all recorded crimes in the city, it does provide a good measure of crime during the pandemic period, one that has been used in other COVID-19/crime-related studies (Bullinger et al, 2020 ; Dai et al, 2021 ). The data includes eight typical property offenses: automobile theft, electromobile (also referred to as electric scooters) theft, motorcycle theft, bicycle theft, theft from automobiles, residential burglary, cyber-fraud, and pickpocketing.…”
Section: Methodsmentioning
confidence: 99%
“…A few recent studies have revealed some general information on policing during the pandemic in China. For instance, one study analyzed changes in calls for police service during the lockdown in a county-level city in Hubei province and found that traffic, disputes, and crime calls reduced, whereas domestic violence and public security calls increased (Dai et al, 2021 ). Other descriptive studies asserted that the police had experienced an increase in COVID-19 related crime, such as producing and selling fake medical devices, price gauging, and online and telephone fraud (Jiang & Xie, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic brought dramatic changes to recorded crime patterns and trends in many countries (Abrams, 2021 ; Andresen & Hodgkinson, 2020 ; Ashby, 2020a , 2020b ; Borrion et al, 2020 ; Dai et al, 2021 ; Hoehn-Velasco et al, 2020 ; Estévez-Soto, 2020 ; Gerell et al, 2020 ; Campedelli et al, 2020 ; Andresen & Hodgkinson, 2020 ; Nivette et al, 2021 ; Payne et al, 2020 , 2021 ; Piquero et al, 2020 ; Wang et al, 2021 ). For the most part, lockdowns and social distancing restricted the movement of people in ways that disrupted and caused sharp declines in recorded crime types.…”
Section: Introductionmentioning
confidence: 99%